Angiotensin-converting enzyme gene polymorphism in arrhythmogenic right ventricular dysplasia: is DD genotype helpful in predicting syncope risk? - FAK, ALİ SERDAR; ÖZBEN SADIÇ, BESTE (SAGE PUBLICATIONS LTD, 2008)
Introduction. Arrhythmogenic right ventricular dysplasia (ARVD) is a heritable disorder characterised by fibrofatty replacement of right ventricular myocytes and increased risk of ventricular arrhythmias and sudden cardiac death. Angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D)) polymorphism affects myocardial ACE levels. DD genotype favours myocardial fibrosis and is associated with malignant ventricular tachycardia. The aim of this study was to explore ACE gene polymorphism in ARVD patients. Methods. Twenty-nine patients with ARVD and 24 controls were included. All ARVD patients had documented sustained ventricular tachycardia, Thirteen patients had syncopal episodes. Six patients were resuscitated from sudden cardiac death. ACE gene polymorphism was identified by polymerase chain reaction technique. Results. There was no significant difference in DD genotype frequency between ARVD patients and controls (44.8% vs. 45.8%, p=0.94). However, DD genotype frequency was significantly higher in ARVD patients with syncopal episodes compared to those without syncope (69.2% vs. 25.0%, p=0.017, odds ratio: 6.750, 95% confidence interval: 1.318-34.565). DD genotype was detected in higher frequency also in patients with a family history of sudden cardiac death (66.7% vs. 39.1%, p=0.36). Conclusion. High prevalence of DD genotype in ARVD patients with syncope suggests that ACE I/D polymorphism might be useful in identifying high-risk patients for syncope.
Keywords: angiotensin-converting enzyme gene pollymorphism; arrhythmogenic right ventricular dysplasia; sudden cardiac death; syncope; ventricular tachycardia; INSERTION DELETION POLYMORPHISM; ESSENTIAL-HYPERTENSION; SUDDEN-DEATH; WOOLLY HAIR; CARDIOMYOPATHY; ASSOCIATION; ARRHYTHMIAS; MUTATIONS; DISEASE; DYSPLASIA/CARDIOMYOPATHY